Effective factors in non-compliance with therapeutic orders of specialists in outpatient clinics in Iran: a qualitative study - Soheila Naghavi; Mohammad Hossein Mehrolhassani; Nouzar Nakhaee; Vahid Yazdi-Feyzabadi (BMC, 2019)
Abstract Background Non-compliance with prescribed treatment is an important cause of preventable mortality and economic burden. Recognition of the factors for non-compliance with the therapeutic orders of specialists from the perspective of patients and health care providers sheds more light on the issue for policymakers and stakeholders. The current study aimed at determining the factors for non-compliance with therapeutic orders in outpatient clinics in Kerman, Iran. Methods The current qualitative study was conducted using the phenomenological method and semi-structured interviews with 10 patients, five specialists, and four health care managers and treatment officials in outpatient clinics in Kerman. The interviewees were selected by purposive sampling. The codes extracted from the interviews were transcribed using conventional content analysis to identify the viewpoints. The MAXQDA 10 software was used to analyze the data. Results The reasons for non-compliance with specialists' orders were categorized into five themes including patient-related (patient-centered), disease-related, therapy-related, the healthcare provider related (healthcare system), and socioeconomic factors. Themes were composed of fifteen categories and forty-one sub-categories. The dominant sub-categories extracted from interviews were health literacy and knowledge of the patient, communication and patients' trust in physicians and direct costs of treatment. Conclusion This study identified a wide range of different individual, disease, treatment, health care provider, and socio-economic factors and the interactions between them which may result into non-compliance with therapeutic orders prescribed by specialists. Therefore, specific attention should be paid to integrate the service provision system into the collaborative approach of the patient and his/her family in order to promote the level of compliance with therapy and care in planning and policy-making to improve the health service provision system.